1995
DOI: 10.2170/jjphysiol.45.1043
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Heat Production of Brown Adipocytes via Typical and Atypical .BETA.-Adrenoceptors in the Rat.

Abstract: Previous studies in our laboratory demonstrated that microcalorimetry is an appropriate method for estimating the physiological function of isolated rat brown adipocytes. In the present study, to elucidate the mode of action of typical and atypical beta-adrenoceptors on heat production of this cell, the effect of novel adrenergic beta 3-agonists was compared with that of other typical adrenergic reagents by direct microcalorimetry. Isoproterenol and beta 3-agonists, BRL37344, ICI215001, and CGP12177, increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
10
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
5
10
0
Order By: Relevance
“…This would be advantageous to animals resistant to a hot environment. In a previous paper, we demonstrated that 10 9 M isoproterenol increased heat production in Wistar rats [17,18]. In the present study, an equivalent result was obtained in WKAH rats, but not in FOK rats, at both normal and high temperatures.…”
Section: Unpaired T-test)supporting
confidence: 74%
See 3 more Smart Citations
“…This would be advantageous to animals resistant to a hot environment. In a previous paper, we demonstrated that 10 9 M isoproterenol increased heat production in Wistar rats [17,18]. In the present study, an equivalent result was obtained in WKAH rats, but not in FOK rats, at both normal and high temperatures.…”
Section: Unpaired T-test)supporting
confidence: 74%
“…Since in heat-acclimated animals, it was found that certain suppressive modifications of the metabolic oxidative processes took place [2,4,13,21], it may be assumed that similar changes would occur in FOK rats without exposure to heat. The high concentration (10 6 M) of isoproterenol was thought to be the maximal stimulation [17,18], where the maximal heat production was similar between the two strains.…”
Section: Unpaired T-test)mentioning
confidence: 99%
See 2 more Smart Citations
“…In this respect, isoprenaline-induced responses are therefore principally different from those of selective ␤ 3 -agonists, for which we see no indication of an ␣ 1 effect. It is possible that this ␣ 1 -component may explain several recent observations on brown fat cells where the response to isoprenaline deviated from that to selective ␤ 3 -stimulation or direct adenylyl cyclase activation (41)(42)(43). That isoprenaline seems to influence the ␣ 1 -pathway to a larger extent in brown fat cells than in many other tissues may be due to the very high level of expression of ␣ 1 -receptors in brown adipose tissue, compared with the levels in other tissues (44).…”
Section: Discussionmentioning
confidence: 99%